Cost-effectiveness of rotavirus vaccination in Albania. (7th May 2015) - Ahmeti, Albana; Preza, Iria; Simaku, Artan; Nelaj, Erida; Clark, Andrew David; Felix Garcia, Ana Gabriela; Lara, Carlos; Hoestlandt, Céline; Blau, Julia; Bino, Silvia
Highlights: Rotavirus RV1 and RV5 vaccines would avert 51, 172 outpatient visits and 14, 200 hospitalizations. Each vaccine would avert a total of 27 deaths, 950 DALYs and gain 801 life years. Total cost of RV1 and RV5 vaccines would be US 5.77 and US 8.66 million, respectively. Introduction of RV1 vaccine would be a highly cost-effective approach in Albania. Abstract: Background: Rotavirus vaccines have been introduced in several European countries but can represent a considerable cost, particularly for countries that do not qualify for any external financial support. This study aimed to evaluate the cost-effectiveness of introducing rotavirus vaccination into Albania's national immunization program and to inform national decision-making by improving national capacity to conduct economic evaluations of new vaccines. Methods: The TRIVAC model was used to assess vaccine impact and cost-effectiveness. The model estimated health and economic outcomes attributed to 10 successive vaccinated birth cohorts (2013–2022) from a government and societal perspective. Epidemiological and economic data used in the model were based on national cost studies, and surveillance data, as well as estimates from the scientific literature. Cost-effectiveness was estimated for both the monovalent (RV1) and pentavalent vaccines (RV5). A multivariate scenario analysis (SA) was performed to evaluate the uncertainty around the incremental cost-effectiveness ratios (ICERs). Results: With 3% discounting of costs and health benefits over the period 2013–2022, rotavirus vaccination in Albania could avert 51, 172 outpatient visits, 14, 200 hospitalizations, 27 deaths, 950 disability-adjusted life-years (DALYs), and gain 801 life-years. When both vaccines were compared to no vaccination, the discounted cost per DALY averted was US 2008 for RV1 and US 5047 for RV5 from a government perspective. From the societal perspective the values were US 517 and US 3556, respectively. Conclusion: From both the perspectives, the introduction of rotavirus vaccine to the Albanian immunization schedule is either cost-effective or highly cost-effective for a range of plausible scenarios. In most scenarios, including the base-case scenario, the discounted cost per DALY averted was less than three times the gross domestic product (GDP) per capita. However, rotavirus vaccination was not cost-effective when rotavirus cases and deaths were based on plausible minimum estimates. Introduction of RV1 would yield similar benefits at lower cost.